Study of Therapeutic Potential of Cryopreserved Newborn Rat Neural Cells in Rat Model of Intracerebral Hemorrhage - Zolotko, Kyrylo M.; Sukach, Oleksandr M. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 054–058